USING READING ALOUD TO DEVELOP STUDENTS' READING SKILL - Sunardi (Language and Education Journal, 2018)
Reading is one of the four skills that the students should master. Since reading is still difficult for students to learn; therefore, the objective of this study was to find out whether or not there was a significant difference in reading achievement between the students who were taught using reading aloud and those who were not. The population of this study was all the eighth-grade students at SMP Negeri 1 Pedamaran. The sample of this study was 65 students of two classes, class VIII 2 as the experimental group consisted 32 students, class VIII3 as the control group consisted 33 students. The experimental method was used to conduct to study. The data obtained were analyzed by using t-test. The result of the data showed that mean score posttest of the experimental group was 84.88 while mean score posttest of the control group was 54.18. Based on the result of independent sample t-test, the significant level was 0.000 (P<.000). Since P < .000 was lower than alpha value 0.05, it meant that the research hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It can be concluded that there was a significant difference in reading achievement between the students who were taught through reading aloud technique and those who were not